Survey and analysis of willingness to use mobile medical services and influencing factors of TB patients treated at home - Chen, Xiao-Feng; Nie, Fei-Fei; Jiao, Xiao-Ke; Lv, Chen; Sun, Juan; Wang, Xiu-jun; Wang, Xiu-Hua; Zhang, Ning (The Journal of Infection in Developing Countries, 2023)
Introduction: The objective of this study was to investigate the willingness of patients with tuberculosis (TB) to use mobile medical services (mHealth) and its influencing factors, so as to provide theoretical guidance for optimizing the TB mobile medical platform and improve the willingness of patients to use mHealth. Methodology: In this cross-sectional study, convenience sampling method was used to investigate patients with TB from the outpatient clinics of two TB specialized hospitals (Beijing Thoracic Tumor and Tuberculosis Hospital and Tuberculosis Prevention and Treatment Hospital of Shaanxi Province) from January to June 2021 using a self-designed questionnaire. Results: Out of 231 patients, only 90 (38.96%) were aware of mHealth services, and 63 (27.27%) had used mHealth services. Among the 63 patients who had used mHealth services, the proportion of mobile medical forms based on WeChat platform was 74.89%. Patients' willingness to use mHealth was scored (11.49 ± 2.53). Univariate analysis showed that the scores of patients' willingness to use mHealth differed by gender and the different ways of affording healthcare (p < 0.05). Regression analysis showed that the influencing factors of willingness to use mHealth in patients with TB included attitude towards use (0.750), health beliefs (0.091) and social impact (0.169) (adjusted R2 = 0.781, p < 0.001). Conclusions: Patients' awareness of the advantages of the new medical model needs to be improved. Optimized design can improve the willingness of patients to use mHealth services and improve the role of mHealth in patient management.